Analisa Pembebanan Statik Pada Fuselage Wahana Terbang Tanpa Awak Atha Mapper 2150 Dengan Simulasi Ansys - Jefri Albukhari; Kaspul Anuar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Fuselage is the main structure of unmanned aerial vehicles where as an electronic space, payload, and as a wing support and tail of the ride. Fuselage is charged during take-off, cruise, and landing. One of the charges on the fuselage is the mass pressure of the electronic as well as the transported payload. This study aims to find out the strength of the structure on the fuselage design of the Atha Mapper 2150 unmanned vehicle. Simulation of the strength of the fuselage design structure of the Atha Mapper 2150 unmanned vehicle was conducted with the help of Ansys software. From the results of the simulation of the strength of the structure in the fuselage design obtained the maximum deflection value occurred at 0.25816 mm (in the middle of the fuselage), the maximum voltage occurred at 1,876 MPa (wing connection with fuselage) and the minimum safry factor value of 15.Keywords: Atha Mapper 2150, Fuselage, Structur.